Microdosimetry for a carbon ion beam using track-etched detectors - Ambrožová, I; Vondráček, V; Šefl, M; Štěpán, V; Pachnerová Brabcová, K; Ploc, O; Incerti, S; Davídková, M (Radiation protection dosimetry, 2015)
Track-etched detectors (TED) have been used as linear energy transfer (LET) spectrometers in heavy ion beams for many years. LET spectra and depth-dose distribution of a carbon ion beam were measured behind polymethylmethacrylate degraders at Heavy Ion Medical Accelerator in Chiba, Japan. The measurements were performed along monoenergetic beam with energy 290 MeV u(-1) in different positions: (1) at beam extraction area, (2) at beginning, (3) maximum and (4) behind the Bragg peak region (0, 117, 147 and 151 mm of water-equivalent depth, respectively). The LET spectra inside and outside of the primary ion beam have been evaluated. TED record only heavy charged particles with LET above 8-10 keV µm(-1), while electrons and ions with lower LET are not detected. The Geant4 simulation toolkit version 4.9.6.P01 has been used to estimate the contribution of non-detected particles to absorbed dose. Presented results demonstrate the applicability of TED for microdosimetry measurements in therapeutic carbon ion beams.
Keywords: Equipment Design; Heavy Ions; elektrony; částice - urychlovače; počítačová simulace; Radiometry; polymethylmethakrylát; Calibration; Electrons; radiometrie; Computer Simulation; kalibrace; Linear Energy Transfer; Microtechnology; lineární přenos energie; Polymethyl Methacrylate; těžké ionty; mikrotechnologie; Radiation Dosage; design vybavení; Carbon; uhlík; dávka záření; Particle Accelerators